2003
DOI: 10.1046/j.1360-2276.2003.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Field efficacy of thermally expelled or live potted repellent plants against African malaria vectors in western Kenya

Abstract: Summaryobjective To estimate the effectiveness of live potted plants and thermal expulsion of plant materials in repelling African malaria vectors in traditional houses in western Kenya.methods Ocimum americanum, Lantana camara and Lippia ukambensis were tested in live, intact potted form whereas leaves of Corymbia citriodora, leaves and seeds of O. kilimandscharicum and O. suave were tested by thermal expulsion from modified traditional stoves. A latin square design was applied for randomly assigning the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 25 publications
3
77
0
1
Order By: Relevance
“…[57] Similar studies have been reported in Kenya [56,58] and soap-form ("Faso Soap") repellents has also proven effective in Burkina Faso. [59] Although, rural communities have the skills to prepare, it is considered laborious, [56] making it less organisationally feasible. It is also considered old-fashioned, stains dresses, has bad odour [57] and promotes gender inequity because the burden to prepare is often on the women, hence, unacceptable.…”
Section: Strategies To Address Community Educationsupporting
confidence: 61%
See 2 more Smart Citations
“…[57] Similar studies have been reported in Kenya [56,58] and soap-form ("Faso Soap") repellents has also proven effective in Burkina Faso. [59] Although, rural communities have the skills to prepare, it is considered laborious, [56] making it less organisationally feasible. It is also considered old-fashioned, stains dresses, has bad odour [57] and promotes gender inequity because the burden to prepare is often on the women, hence, unacceptable.…”
Section: Strategies To Address Community Educationsupporting
confidence: 61%
“…[57] Mosquitoes do not bite 52% and 39% of those who use Saccharum officinarum and Ocimum basilicum (traditional plant repellents) respectively in Cameroon. [57] Similar studies have been reported in Kenya [56,58] and soap-form ("Faso Soap") repellents has also proven effective in Burkina Faso. [59] Although, rural communities have the skills to prepare, it is considered laborious, [56] making it less organisationally feasible.…”
Section: Strategies To Address Community Educationsupporting
confidence: 61%
See 1 more Smart Citation
“…Lucia et al (2007) have also demonstrated that E. globulus essential oil displays toxic effects on Aedes aegypti larvae, these authors determined its LC 50 =32.4 ppm. In relation to this activity, Seyoum et al (2003) have reported that burning of E. citriodora leaves represents a cheap and effective method of household protection against mosquitoes in Africa.…”
Section: Potential Usesmentioning
confidence: 99%
“…citriodora leaves has been traditionally used as insecticide repellent, especially by low income families to protect them against mosquitoes [212].…”
Section: Insecticide Activitymentioning
confidence: 99%